Sosialisasi Bank Sampah untuk Peningkatan Kesadaran Masyarakat Kelurahan Pulo Kerto dalam Mendukung SDG’s 12 - Azhar, Azhar; Sartika, Diana Dewi; Djunaidi, Djunaidi; Putri, Cynthia Azhara; Syuryansyah, Syuryansyah; Amalia, Ridha; Wijaya, Bagaskara Sagita (Universitas Medan Area, 2026)
Waste management is a critical issue in urban areas, including in Pulo Kerto Village, Gandus District, Palembang City. This community service activity aimed to increase residents’ knowledge and awareness of waste banks as a sustainable waste management solution to support the achievement of SDG 12 (Responsible Consumption and Production). The method used was Participatory Learning and Action (PLA), comprising three stages: observation, core implementation (socialization, education, and waste-sorting practice), and evaluation. The activity was attended by 30 participants, consisting of housewives and environmental cadres. Evaluation results showed a significant increase in community knowledge: understanding of the waste bank concept increased from 16% to 100%, waste sorting ability increased from 27% to 80%, and willingness to participate in waste banks increased from 40% to 90%. This activity had a positive impact on changing community attitudes in managing household waste more responsibly.